Acute locked superior shoulder dislocation in a patient with cuff tear arthropathy. (20th June 2018) - Plachel, Fabian; Korn, Gundobert; Abdic, Sejla; Moroder, Philipp
Abstract : In the field of traumatic shoulder dislocations, this report of a 61-year-old female patient discusses the case of an acute locked superior shoulder dislocation in conjunction with a chronic rotator cuff arthropathy resulting from a low-energy fall on the outstretched and abducted arm. Radiological assessment revealed a complex combination of associated bony injuries including a fracture of the upper part of the glenoid and an impaction fracture of the inferior articular surface of the humeral head. Closed reduction and immobilisation were not successful in obtaining joint stability. This unique report highlights the clinical importance of accurate management of bony injuries in traumatic shoulder dislocation.